Compositional and sensory quality of beef and its determination by near infrared - Barragán-Hernández, Wilson Andrés; Mahecha-Ledesma, Liliana; Olivera-Angel, Martha; Angulo-Arizala, Joaquín (Agronomía Mesoamericana, 2021)
Introduction. Beef is a food of high biological value for human nutrition; it is a source of fat, protein, vitamins, and minerals. However, aspects associated with the environmental impact of the production system and association with non-communicable diseases have promoted new protein consumption trends (vegetable, insects, lab protein). So, it is necessary to identify and offer information on the attributes of the meat that favor consumer acceptance quickly and reliably through non-destructive and environmentally friendly techniques such as near-infrared. Objective. To review the experiences associated with the implementation of Near-Infrared Spectroscopy (NIRS) as an alternative in the determination of beef quality. Development. Meat attributes with the greatest relationship with consumers can be segmented into appearance, consumption, and confidence. These characteristics involve intrinsic elements of the meat, such as color, fat, and tenderness. Given the limitations in the application of laboratory techniques for the determination of meat attributes, the application of the NIRS is reviewed with successful experiences in characteristics of interest to consumers. Additionally, the application of NIRS in production lines and other applications of interest in the industry, such as detection of meat anomalies and product authentication, is studied. Conclusion. The application of the NIRS allows to determine quickly and reliably attributes of the quality of the meat that have a close relationship with the consumer. This tool allows to obtain results that respond to the production speed of the industry, and to determinate and authenticate aspects related to meat and the production system.